BIGGER ORGANS and ELEPHANT EAR-LIKE LEAF1 control organ size and floral organ internal asymmetry in pea - Li, Xin (Journal of experimental botany, 2019)
Control of organ size and shape by cell proliferation and cell expansion is a fundamental process during plant development, but the molecular mechanisms that set the final size and shape of determinate organs in plants remain unclear, especially in legumes. In this study, we characterized several mutants including bigger organs (bio) and elephant-ear-like leaf 1 (ele1) in pea that displayed similar phenotypes, with enlarged leaves and symmetrical lateral and ventral petals. Genetic analysis showed that BIO interacted with the specific regulators SYMMETRICAL PETAL1 (SYP1) and SYP5 to control floral organ internal asymmetry in pea. Using a comparative approach, we cloned BIO and ELE1, revealing that they encode a KIX domain protein and an ortholog of Arabidopsis PEAPOD (PPD), respectively. Furthermore, genetic analysis, physical interaction assays, and gene expression analysis showed that BIO and ELE1 physically interact with each other and with the transcription factor LATHYROIDES (LATH) to repress expression of downstream genes such as GROWTH-REGULATING-FACTOR 5. Our data show that the BIO-ELE1 module in legumes plays a key role in regulating organ development to create distinct final forms with characteristic size and shape